Engineering method of assessing temperature and the dynamics of temperature change in the premise heated by a system based on a gas infrared heater - Boris V. Borisov; Alexander V. Vyatkin; Vyacheslav I. Maksimov; Tatiana A. Nagornova (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The operation of any heating systems is determined by the interrelationship of many physical processes. Recently, for heating large premises, it has been increasingly proposed to use heating systems based on gas infrared heaters of various designs. Such systems are most relevant for large industrial premises, as they are capable of creating favorable living and working conditions in a local work area without significant costs for heating the rest of the premise. When designing complex systems, an important factor is the use of simple relationships to assess the trends of average values ​​of parameters aimed at achieving the desired result. There is a need to set the main dimensionless criteria that determine a particular process within the framework of similarity theory. Aim. To state the basic relationships and dimensionless criteria for analytical engineering assessment of the average temperature over the volume of a premise and the dynamics of its change during heating the premise by a system based on the gas infrared heaters. Objects. Heating system with gas infrared heaters. Methods. Mathematical modeling was carried out within the framework of a 0D mathematical formulation. Results. The authors have stated the main relationships and dimensionless criteria for the analytical assessment of temperature and the dynamics of its change during heating of the premise by a system based on a gas infrared heater on the basis of the approach averaged over the entire volume of the premise. The results of calculations according to the obtained relationships are presented in comparison with the results of calculations according to the full 0D model, which are verified on the results of 2D modeling and experimental measurements.